A Sustainable Energy Management Evaluation and Decision-Making Framework of Hybrid Solar Geyser-Stove System in Domestic buildings - Muhammad Nauman Fazal; Abdullah Altamimi; Syed Ali Abbas Kazmi; Zafar A. Khan; Faisal Asfand (Results in Engineering)
In an era characterized by mounting environmental concerns and growing demand for sustainable energy solutions, this study comprehensively evaluates hybrid solar geyser and stove systems tailored for the domestic building sector. This study assesses hybrid solar geyser and stove systems across techno-economic and environmental dimensions by utilizing the Multi-Criteria Decision-Making (MCDM) framework, focusing on energy efficiency, cost-effectiveness, environmental sustainability, and user comfort. The hardware setup includes the integration of solar panels, storage batteries, and heating elements to harness solar energy for cooking and water heating. Furthermore, incorporating the Internet of Things (IoT) system for controlling solar geysers and stove systems through mobile application presents a promising avenue for enhancing system functionality and user experience. The MCDA analysis showed that alternative 5 (Direct DC stove) demonstrated the highest energy efficiency (0.9136), lowest load loss factor (15.2465 W), and superior environmental sustainability (173.41g/kWh for gas). This study also demonstrates minimal load loss and energy unreliability considering different factors, making it a highly effective and sustainable choice for domestic applications. The outcomes of the framework analysis contribute valuable information for stakeholders, policymakers, and businesses seeking to make informed choices in adopting sustainable solutions. Policy and regulatory implications are thoroughly examined, providing useful insights for policymakers and stakeholders seeking to promote sustainable energy practices.